Urban nature : poems about wildlife in the city - Laure-Anne Bosselaar (Minneapolis, MN : Mlikweed Editions, 2000)
Deep in the concrete canyons of even the largest cities, nature lurks. Its unpredictable energies animate not only squirrels and microorganisms, not only ginkgoes, roots, and rivers, but also the engines of human desire. Urban Nature captures the many faces of wildness in the city with poems by more than 130 emerging and recognized poets.
Includes index
Keywords: Nature -- Poetry; City and town lifes; Human ecology